Kontekst w interpretacji metajęzykowych jednostek ironicznych: struktury, typy, granice (na podstawie języka polskiego, rosyjskiego i angielskiego) - Starodvorskaia, Ekaterina (Studia Rossica Posnaniensia, 2023)
The paper deals with the role of context and its features in the interpretation of ironically used metalinguistic (reflexive) expressions in the Russian, Polish, and English languages. Although contextual cues have always been a major topic of interest to irony scholars, more research seems to be needed on how context interacts with a metalinguistic expression and how it indicates that such an expression is to be interpreted ironically. It is clear that the most natural context in the situation in question is speech (in a broad sense) that is referred to in particular metalinguistic expressions. Therefore, the main goal of the paper is to establish the crucial features of linguistic units that could be named and described by metalinguistic expressions and to specify relations between the former and the latter. The main criteria used to classify the examples that are analyzed in the paper are 1) the type of the linguistic unit in the context, 2) the type of contradiction between the metalinguistic expression and the context, and 3) the limits of the context that is required for ironical interpretation of the metalinguistic expression.